Clinico-pathological and prognostic overview of metastasizing ameloblastoma: An overview of the systematic reviews - Gargi Sarode; Shailesh M. Gondivkar; Akanksha Gore; Rahul Anand; Namrata Sengupta; Vini Mehta; Sachin C. Sarode (Journal of Oral Biology and Craniofacial Research)
Background: Metastasizing Ameloblastoma (MA) is an aggressive variant of ameloblastoma (AM) with the ability to metastasize without cytological malignant changes. Thus it aims to comprehensively review the clinico-pathological and prognostic aspects of MA through integration of current literature. Methods: Electronic searches were conducted in PubMed-MEDLINE, Scopus, Web of Science and Google Scholar. Two independent reviewers screened abstracts and evaluated paper eligibility. AMSTAR2 checklist was used to assessed methodological quality of included systematic reviews (SRs). Results: From 390 initial papers, 279 underwent eligibility screening, with five systematic reviews (SRs) meeting inclusion criteria. Six hundred sixty-one MA cases were found in five SRs that were included. MA predominantly affects men, exhibits mandible preference, and occurs in individuals in their fourth or fifth decade. Benign metastatic deposits commonly manifest in lungs and lymph nodes. Distant metastasis probability rises with multiple recurrences and incomplete surgical removal. Tumor recurrence and metastasis unfavorably impact clinical outcomes. Quality of evidence assessment was absent across SRs; four SRs were critically low in methodological quality. Conclusions: AM's metastatic potential lacks predictability. Early/multiple recurrences post-treatment may signal poor prognosis, warranting vigilant follow-up. Methodical analysis of each AM case is imperative to comprehend the metastatic-benign histology relationship.